A study on natural rubber composites reinforced by carbon fiber. Issue 1 (May 2020) - Zhang, Qiong; Li, Yi; Zhu, Pengxiao; Yuan, Song
Abstract: The carbon fiber was used to reinforce the natural rubber. The mechanical property, thermal property, morphology and thermal conducting property of the rubber composites were researched. The carbon fiber is dispersed well in the rubber matrix according to the scanning electron microscope images. The strength increased with the increase of the carbon fiber content and the strength reached the maximum value 20.9MPa when the content of carbon fiber is 2%. The addition of carbon fiber improves the aging resistance of rubber and maintain the property of rubber matrix. The addition of carbon fiber can improve the decomposition temperature effectively and enhance the heat-conducting property.